ORGANISATIONAL EFFECTIVENESS OF THE EDUCATION DISTRICT IN CURRICULUM DELIVERY - Sadie, Stephen (My University, 2011)
The district plays a key role in the education system. It is one of the few places that can drive systemic reform in schools, yet even the legislation is silent on the powers of the district. Not only have districts been neglected in research but much of the existing research on districts was considered to be sketchy and superficial. This research attempts to do an in-depth study of one district only i.e. the Johannesburg East District. The key aim of the research is to provide a set of systematic recommendations for improved practice. The research method was a survey. There were two phases to the research. The first phase was a survey while the second phase provided a set of recommendations. This study is set against the theoretical backdrop of organisation development and change management. Organisation development and change management specifically aim to improve the effectiveness of organisations. A key principle here is that the people (district officials) who are expected to make the change are fully involved in the process. Therefore a questionnaire was distributed to all 51 district curriculum officials. Of the 51 questionnaires that were handed out, 49 were returned. The questionnaire was designed around the „McKinsey Seven-S Framework‟ which provided a holistic way of analysing the organisational effectiveness of the district. The key questions were taken from the most important issues that emerged in the literature review. The research found that strategy, systems and skills were basically functional. However, structure, style, staff and shared values need urgent attention. Improved communication is a key recommendation of this study. A synthesising model is developed which summarises the main findings of this study. These findings were crystallised from a lengthy process of analysis. It is hoped that this study will point the way towards more effective district curriculum delivery
MBA thesis - WBS
Keywords: Education districts; Curriculum delivery